Facile design of plant-oil-infused fine surface asperity for transparent blood-repelling endoscope lens. Issue 53 (16th May 2016) - Nishioka, Sachiko; Tenjimbayashi, Mizuki; Manabe, Kengo; Matsubayashi, Takeshi; Suwabe, Ken; Tsukada, Kosuke; Shiratori, Seimei
Abstract : Minimally invasive medical operations, especially endoscope operations, have attracted much attention and play a major role in modern medicine. Abstract : Minimally invasive medical operations, especially endoscope operations, have attracted much attention and play a major role in modern medicine. Endoscope operations are superior to decrease incisions, enabling good post-operation progress. However, during its implementation, blood adheres to the lens of the endoscope, resulting in obstructed vision. This prolongs the operation time and causes the patient to gain weight. Hence, we developed a blood-repelling and transparent material for coating the surface of an endoscope lens. The coating material was produced from plant oil and a rough material for trapping the oil. Edible plant oil was particularly used to enable application to medical devices. A fine surface asperity was achieved by a one-dip treatment, which also enhanced the capillary force and durability of the oil under a water shower. The application of the developed coating material to an endoscope lens in an animal experiment enabled the effective repulsion of blood and other body fluids, the maintenance of a clear vision, and high transmittance. The developed coating material promises to contribute to the achievement of antifouling surfaces in medical devices.